Neurological findings in autosomal dominant polycystic kidney disease - Yıldız, Demet; Yıldız, Abdülmecit (The European Research Journal, 2019)
Objective: Autosomal dominant polycystic kidney disease (ADPKD) mainly affects the kidneys, but other abnormalities like intracranial aneurysms (ICAs) are not uncommon. In this study, we aimed to investigate retrospectively frequency of ICA and other neurological abnormalities in ADPKD patients. Methods: One hundred and forty patients with ADPKD who did not receive replacement therapy and followed-up at outpatient clinic were evaluated. Results: The mean age of the patients was 43.4 ± 13 years and mean glomerular filtration rate was 87 ± 15 ml/min. ICA was detected in four (2.8%) patients. Three patients were from the same family. Thirteen (9.3%) patients had magnetic resonance angiography due to their family stories, but aneurysm was not seen in them. Conclusion: Individuals with ADPKD who have a history of aneurysm or hemorrhage in their family should be screened for aneurysm due to mortality and risk of recurrent rupture.